Model systems for studying cell adhesion and biomimetic actin networks - Brüggemann, Dorothea; Frohnmayer, Johannes P.; Spatz, Joachim P. (Beilstein Journal of Nanotechnology, 2014)
Many cellular processes, such as migration, proliferation, wound healing and tumor progression are based on cell adhesion. Amongst different cell adhesion molecules, the integrin receptors play a very significant role. Over the past decades the function and signalling of various such integrins have been studied by incorporating the proteins into lipid membranes. These proteolipid structures lay the foundation for the development of artificial cells, which are able to adhere to substrates. To build biomimetic models for studying cell shape and spreading, actin networks can be incorporated into lipid vesicles, too. We here review the mechanisms of integrin-mediated cell adhesion and recent advances in the field of minimal cells towards synthetic adhesion. We focus on reconstituting integrins into lipid structures for mimicking cell adhesion and on the incorporation of actin networks and talin into model cells.
Keywords: actin network; cell adhesion; giant unilamellar vesicle; integrin; lipid bilayer; synthetic cell; protein reconstitution; talin